(untitled) (Research, Society and Development, 2021)
Exposure to hypergravity can alter the viability, morphology, development and behavior of living beings. Thus, the analysis of these factors is essential when considering life on supermassive planets, as well as in ’ballistic panspermia’ scenarios related to the ejection of rocks from the surface of a planet, which could serve as transfer vehicles to spread the life between planets within a solar system. Studies analyzing the effects of hypergravity regimes are abundant in the literature, however, only a few researches carried out experiments using conditions of the order of 105 x g. In addition, the only plant species tested so far, as an entire structure instead of detached parts, exposed to gravity stress of this order of magnitude in its entirety was Oryza sativa, whose seeds were able to germinate after being exposed to 450,000 x g. Recently, our research group demonstrated that some free-living nematode species can support 400,000 x g. In the present study, we report that seeds of the plant model Nicotiana benthamiana exposed to 400,000 x g for 1h are able to germinate into fully normal young seedlings, with no apparent morphological alterations. Since N. benthamiana is used in laboratories worldwide and an easy to cultivate plant model, theoretical and experimental models of lithopanspermia and life in supermassive planets may benefit from it.